Crowdsourcing Electronic Health Record Improvements at Scale across an Integrated Health Care Delivery System - Rajamani, Geetanjali; Diethelm, Molly; Gunderson, Melissa A.; Talluri, Venkata S. M.; Motz, Patricia; Steinhaus, Jennifer M.; LaFlamme, Anne E.; Jarabek, Bryan; Christiaansen, Tori; Blade, Jeffrey T.; Badlani, Sameer; Melton, Genevieve B. (Applied Clinical Informatics, 2023)
Background and Objective Despite widespread adoption of electronic health records (EHRs), these systems have significant room for improved efficiency and efficacy. While the idea of crowdsourcing EHR improvement ideas has been reported, little is known about how this might work across an integrated health care delivery system in practice.Methods Our program solicited EHR improvement submissions during two timeframes across 10 hospitals and 60 clinics in an upper-Midwest integrated health care delivery system. Submissions were primarily collected via an EHR help feature.Results A total of 262 and 294 submissions were received in 2019 and 2022, with a majority initiated from physicians (73.5 and 46.9%, 2019 and 2022) specializing in family medicine (52.0 and 59.3%). In 2022, the program reached a larger variety of personnel than 2019, with 53.0% of submissions from advanced practice providers, nurses, administrative staff, and other roles (p < 0.0001). Many ideas (36.4 and 50.0% in 2019 and 2022) reflected a lack of user understanding of EHR features and were addressed through training/education. Significant (27.1 and 25.9%) or simple (24.0 and 14.7%) EHR optimizations were required to address most remaining suggestions, with a number part of planned EHR improvement projects already (16.3 and 17.6%).Conclusion Our experience using a crowdsourcing approach for EHR improvement ideas provided clinicians and staff the opportunity to address frustrations with the EHR and offered concrete feedback and solutions. While previous studies have suggested EHR technology improvements as paramount, we observed large numbers of users having a misunderstanding of EHR features, highlighting the need for improved EHR user competency and training.
Keywords: electronic health records; clinical documentation; training and education; burnout; crowdsourcing; documentation burden